Evaluation of Pachymetric Measurements with Scheimpflug Photography-Based System and Optical Coherence Tomography Pachymetry at Different Stages of Keratoconus - Betül İlkay Sezgin Akçay; Engin Bilge Özgürhan; Ercüment Bozkurt; Tuğba Kurt; Yusuf Yıldırım; Mediha Gülen Coşar; Aydın Yıldırım; Jülide Canan Umurhan Akkan; Ahmet Demirok (Journal of Ophthalmology)
The aim of this study was to compare the central and peripheral pachymetric measurements determined with Sirius system and Visante OCT and evaluate the agreement between them at different stages of keratoconus. Measurements were not significantly different in all patients and subgroups and showed high correlation for the corneal thicknesses of the entire cornea in different stages of keratoconus.